Long-Term Natural History and Complications of Collagenous Colitis - Hugh J Freeman (Canadian Journal of Gastroenterology)
Microscopic forms of colitis have been described, including collagenous colitis, a possibly heterogeneous disorder. Collagenous colitis most often appears to have an entirely benign clinical course that usually responds to limited treatment. Sometimes significant extracolonic disorders, especially arthritis, spondylitis, thyroiditis and skin disorders, such as pyoderma gangrenosum, dominate the clinical course and influence the treatment strategy. However, rare fatalities have been reported and several complications, some severe, have been attributed directly to the colitis. Toxic colitis and toxic megacolon may develop. Concomitant gastric and small intestinal inflammatory disorders have been described including celiac disease and more extensive collagenous inflammatory disease. Colonic ulceration has been associated with the use of nonsteroidal anti-inflammatory drugs, while other forms of inflammatory bowel disease, including ulcerative colitis and Crohn disease, may evolve directly from collagenous colitis. Submucosal ‘dissection’, colonic fractures, or mucosal tears and perforation, possibly from air insufflation during colonoscopy, have been reported. Similar changes may result from increased intraluminal pressures that may occur during radiological imaging of the colon. Neoplastic disorders of the colon may also occur during the course of collagenous colitis, including colon carcinoma and neuroendocrine tumours (ie, carcinoids). Finally, lymphoproliferative disease has been reported.